Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 350,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

OE: From statement (1) it is clear that \(p=q\) , so the initial difference is 0. Absolutely enough. Statement (2) doesn't give any additional information. So, the answer is A.

In #2, q = -p, or the opposite of p. So p + q = 0, then if p = 2, then q = -2. So that 2 + -2 = 0. Works. Now apply this to \(p^3 - q^3\)

First try p = 2 and q = -2: \(2^3 - (-2)^3 = 8 - - 8 = 16\)

Now try p = -2 and q = 2: \((-2)^3 - 2^3 = -8 - 8 = -16\)

In both situations, p + q = 0, but when used in the equation given in the stem, we get different values so the statement cannot be sufficient, and therefore, A must be the answer since B is insufficient.

x-ALI-x wrote:

DS Question, I don't buy the answer.

Question: What is the value of \(p^3 - q^3\) ?

1. \(p - q = 0\) 2. \(p + q = 0\)

I answered D. Reasoning: \(p^3 - q^3\) = (p - q) (p + q) (p - q)

OA is A. OE: From statement (1) it is clear that \(p=q\) , so the initial difference is 0. Absolutely enough. Statement (2) doesn't give any additional information. So, the answer is A

_________________

------------------------------------ J Allen Morris **I'm pretty sure I'm right, but then again, I'm just a guy with his head up his a$$.

I answered D. Reasoning: \(p^3 - q^3\) = (p - q) (p + q) (p - q) statement 1: (p-q) = 0, then \(p^3 - q^3 = 0\) statement 2: (p+q) = 0, then \(p^3 - q^3 = 0\)

Am I missing something?

OA is A. OE: From statement (1) it is clear that \(p=q\) , so the initial difference is 0. Absolutely enough. Statement (2) doesn't give any additional information. So, the answer is A

In fact, you got incorrect formula for p^3 - q^3. it is:

OA is A. OE: From statement (1) it is clear that \(p=q\) , so the initial difference is 0. Absolutely enough. Statement (2) doesn't give any additional information. So, the answer is A.

Its A. p^3 - q^3 = (p-q)(p^2+q^2+pq) hence 1 is enough.

\((p-q)^3=p^3-q^3-3pq(p-q)\) \(p^3-q^3=(p-q)^3+3pq(p-q)\) case 1.\(p-q =0\) \(p^3-q^3=(0)^3+3pq(0)\) \(p^3-q^3=(0)\) case 2. \(p+q=0\) implies \(p=-q\) \(p^3-q^3=(-q-q)^3+3(-q)q(-q-q)\) \(p^3-q^3=-8q^3+6q^3\) \(p^3-q^3=-2q^3\) (which is dependent on value of q : insufficient)

Seems A is right _________________

Sun Tzu-Victorious warriors win first and then go to war, while defeated warriors go to war first and then seek to win.

OA is A. OE: From statement (1) it is clear that \(p=q\) , so the initial difference is 0. Absolutely enough. Statement (2) doesn't give any additional information. So, the answer is A.

Yes you are missing something and that is the correct factorization of \(p^3 - q^3\) which is \((p-q)*(p^2+p*q+q^2)\).

And as the p+q is not a factor we won't be able to get an answer based on p+q=0 so st2 is insufficient. _________________

\(x^3-y^3=(x-y)(x^2+xy+y^2)\) (and \(x^3+y^3=(x+y)(x^2-xy+y^2)\)), but if you don't know this formula you can do just by substitution, which might be an easier way:

(1) \(p-q=0\) --> \(p=q\) --> \(p^3-q^3=p^3-p^3=0\). Sufficient. (2) \(p+q=0\) --> \(q=-p\) --> \(p^3-q^3=p^3-(-p^3)=2p^3\), so the value we are looking for depends on the value of \(p\). Not sufficient.